Quelques commentaires sur le secteur extérieur de CANDIDE (version 1.1) - Van Peeterssen, Alain (L'Actualité économique, 1976)
AbstractThe following ill-tempered article provides a review of the foreign sector of CANDIDE; after briefly commenting the disagregation by products and services, the author examines the geographical disagregation of imports and exports into and from Canada between the U.S. and the Rest-of-the-World. He found that the proposed CANDIDE procedure is not after all that much meaningful and does not bring any additional information, while being dangerous as far as the forecasters using this model hope to get good results for imports from and exports to the Rest-of-the-World. Finally, the author gives some hints about what could have been alternatively done about this problem of geographical disagregation.